2022
DOI: 10.21873/cdp.10175
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Single Nucleotide Polymorphisms in Papillary Thyroid Carcinoma

Abstract: Thyroid carcinoma represents a leading malignancy among those derived from human endocrine systems. It comprises a variety of different histological subtypes, including mainly papillary carcinoma, follicular carcinoma, anaplastic carcinoma, and medullar carcinoma. A broad spectrum of genetic imbalances, comprising gross chromosomal (polysomy/aneuploidy) and specific gene (mutations, amplifications, deletions) alterations, has been reported. Interestingly, the role of isolated, specific gene polymorphisms, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The term polymorphism refers to the presence in two or more variant forms of a specific DNA sequence in different individuals. Single-nucleotide polymorphisms (SNPs) are the most common type of polymorphisms that involve variations in a single nucleotide [30]. It is known that the presence of SNPs within the coding regions of genes can modify the amino acid sequence of the encoded products causing non-synonymous substitutions that can alter protein structure, then impairing its function [31,32].…”
Section: Role Of Nqo1 Polymorphisms In Ovarian Cancermentioning
confidence: 99%
“…The term polymorphism refers to the presence in two or more variant forms of a specific DNA sequence in different individuals. Single-nucleotide polymorphisms (SNPs) are the most common type of polymorphisms that involve variations in a single nucleotide [30]. It is known that the presence of SNPs within the coding regions of genes can modify the amino acid sequence of the encoded products causing non-synonymous substitutions that can alter protein structure, then impairing its function [31,32].…”
Section: Role Of Nqo1 Polymorphisms In Ovarian Cancermentioning
confidence: 99%
“…Nucleotide changes in various gene locations may lead to carcinogenesis by either the overactivation of oncogenes or by silencing the suppressor genes. Germline mutations occur familiarly, therefore they are inherited, and they can modify the genomic profile, increasing the risk of future cancers, such as thyroid cancer [ 12 , 13 , 14 ].…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%
“…An SNP hosts a variation in the DNA sequence involving a single nucleotide. The mechanism behind these SNPs usually involves point mutations/substitutions, deletions, insertions, or base-pair multiple repeats [ 12 ]. Determining SNPs is a facile and common way to detect genetic variation, making them an easy target for genetic research.…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%
“…SNPs are the most common genetic variations in genome (Stratton MR, 2009) and some heterogeneities in nucleotides can push the sequence of genes into a malignant genotype leading to formation of cancer cells . (Jawad.Z.N and, Awad, W.2020) ( Morphological heterogeneities increase the likelihood of thyroid cancer and its progression, as the study found that it has a significant impact on patients with all types of thyroid cancer (Kaubryte J and Lai AG, 2022) (Kyrodimos, E., et al 2023) The morphological variations in BRAF have an important impact on the formation of tumors and the incidence of different types of cancers as well as thyroid cancer, also its associated with rectal cancer and colon cancer , and affect the size and seriousness of the tumor as well as increase the mortality rate. (Shaalan, A., et al 2022)…”
Section: Introductionmentioning
confidence: 99%